Customer buying experience in multichannel retailing : Transition fluency during customers’ interactions with click-and-mortar furniture and interior design retailers - Panina, Ekaterina (fi=Turun yliopisto|en=University of Turku|, 2017)
Meaningful, memorable and unique customer experiences are proved to influence customer satisfaction and customer loyalty, creating value for companies. However, due to changing multichannel environment and the lack of common understanding of customer experience phenomenon, many retailers struggle to provide their customers with exceptional experiences. This study took on a challenge to conceptualise customer buying experience in multichannel context. The aim of this study was to explore what relevance experience of the multichannel customer during his/her transitions between online and offline retail channels has in customer buying experience. The focus was placed on customer interactions with click-and-mortar furniture and interior design retailers. Multi-method qualitative research design was chosen to explore the phenomena and seek the support for the conceptual framework developed in the literature review. Qualitative data was collected through ten individual semi-structured interviews with consumers and two consumer focus groups, which resulted in 7 hours 12 minutes of audio material. Despite the challenges of approaching such an intangible topic, both data collection methods gave useful insights into the topic of customer buying experience formation. The data was mainly in line with the suggested theoretical model, but also succeeded to develop the model further, bringing the components of customer buying experience closer to service quality components, and emphasising even more the role of channel integration and omnichannel strategies. Basing on the results of this study, several hypotheses for future quantitative research can be proposed. The managerial implications of this study may be useful in the field of specialised multichannel retailing.